PROBLEMATIKA AKAD JUAL BELI PADA FITUR LIVE SHOPPING DENGAN SISTEM FLASH SALE - Ridha Khairani; Nurul Izzah Maulidiyah; Ade Irma Manurung; Ali Imran Sinaga (IJTIMAIYAH Jurnal Ilmu Sosial dan Budaya, 2026)
Abstact: Indonesian positive law. This study analyzes the validity of sales contracts in live shopping flash sales, focusing on defects in consent, gharar, and consumer protection. Using normative legal research with conceptual and statutory approaches, the study finds that system vulnerabilities, phantom flash sales, stock manipulation, and time pressure may violate valid contract principles. From an Islamic law perspective, these practices may contain tadlis, najasy, and gharar. From Indonesian positive law, they may violate consumers’ rights to clear, correct, and honest information. Therefore, stronger regulation and platform accountability are needed to ensure transparency and consumer protection in digital transactions.